Comparison of Antioxidant Activity of Stem Bark, Stem Wood, and Leaf Extracts of Bayur Plant (Pterospermum Subpeltatum C.B.Rob) - Zakaria; Nunuk Hariani Soekamto; Suriani Nur; Ayun Dwi Astuti (Jurnal Penelitian Pendidikan IPA, 2025)
Antioxidants play a role in preventing and repairing damage to human cells. Searches for antioxidant sources continue to be carried out including in P. subpeltatum plants. This study aims to compare the antioxidant activity of the bark, wood, and leaves of P. subpeltatum C.B. Rob plants. The materials were dried and then shaved to a fineness level of 80 mesh. Materials were extracted using the maceration method with ethanol solvent. The macerate was filtered and the filtrate obtained was concentrated with an evaporator. The three extracts were tested for antioxidants using the DPPH (1,1-diphenyl-2-picrylhydrazyl) Free radical scavengers method, ascorbic acid was used as a comparison. Absorbances was measured using UV-Vis spectroscopy. Each material was made in 5 concentrations. The IC50 value was calculated using the Blois regression equation. The results of the antioxidant test were obtained consecutively: stem wood with an IC50 value = 3.39 μg/mL, stem bark = 5.15 μg/mL, and leaf = 258.58 μg/mL, the IC50 value of ascorbic acid was 2.79 μg/mL. Based on these data, it shows that the antioxidant activity of stem wood and stem bark is in the high category, although still lower than ascorbic acid, while the leaf are included in the weak category.